Does Participation in Full-Time Kindergarten Improve Metis Students’ School Outcomes? A Longitudinal Population-Based Study from Manitoba, Canada - Brownell, Emily; Enns, Jennifer E.; Sanguins, Julianne; Brownell, Marni; Chartier, Mariette; Chateau, Dan; Sarkar, Joykrishna; Burland, Elaine; Hinds, Aynslie; Katz, Alan; Santos, Rob; Chartrand, A. Frances; et al. (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2023)
As a result of the colonization of Canada, Metis have faced many political and socioeconomic challenges, one of which is the lower educational achievement of Metis students vs other Canadian students. In this study, we examined whether full-time kindergarten (FTK) vs half-time kindergarten (HTK) was associated with improved educational outcomes for Metis students in Manitoba using linked, population-based administrative data from 1998/99-2012/13. The cohort included 271 FTK and 405 HTK Metis students. We used generalized linear models with binomial distribution to calculate predicted probabilities and risk ratios for the outcomes (assessments of numeracy and literacy in Grades 3, 7 and 8; student engagement in Grade 7; high school graduation). However, we observed no significant differences in outcomes between FTK and HTK students, suggesting that FTK is not sufficient to overcome the structural barriers to academic success Metis students may face.